Vitamin A and dehydrated alfalfa fed individually and in combination with and without Aureomycin in a steer fattening ration - Richardson, D.; Smith, E.F. (Kansas Agricultural Experiment Station, 2011)
This was the second test to compare dehydrated alfalfa as a source of Vitamin A with pre-formed Vitamin A, fed individually and in combination with and without Aureomycin. Two-year-old Hereford steers from two previous bluestem pasture-grazing tests were used in this test. They were from the same group as the yearlings used in the previous test. After the grazing test was completed, the steers were assigned to six lots of nine animals each on the basis of weight and uniformity. Supplements supplied the same amount of protein, calcium and phosphorus in each lot. Vitamin A value of carotene figuring dehydrated alfalfa at 400 I.U. per milligram of carotene gave 10,000 to 12,000 I.U. of Vitamin A per head daily for animals receiving dehydrated alfalfa. Pre-formed Vitamin A was added to the supplements indicated approximately 30 percent loss. Aureomycin was fed at the rate of 70 mgs. per head daily. After the steers were on fall feed, silage was limited to 20 pounds per head daily. The carotene content of the silage averaged about 2mgs. per pound. All the sorghum grain was fed that the steers would clean up.
Keywords: Beef; Vitamin A; Alfalfa; Aureomycin